(untitled) (Medical Forum Monthly, 2024)
Introduction: Fingerprinting is the surest method of human identification and identification is the big problem with particular reference to growing terrorism and crime rate in our country. Objective: To study the fingerprint pattern in the population of Wah Cantt. in connection with the role of fingerprints in identification. Study Design: Cross sectional and observational study. Place and Duration of Study: The study was conducted in the population of Wah Cantt. Total duration of study was three months from 01-09-2013 to 30-11-2013. Material and Methods: A group of 6 Lecturers were trained to take finger prints from different walks of population of Wah Cantt. The fingerprints were taken on unglazed paper with help of ink pad. The data was scrutinized regarding type of fingerprints. The collected data was analyzed by SPSS version 10. Results: A total sample of 1000 persons were taken. Among 596 were male and 404 females. The most common type of finger prints remained loops 56.7 % followed by whorls 27.6 %, Arches 8.4% and composites type of fingerprints were detected in 7.3 % persons. Conclusion: Statistically variations are present in the finger prints as in the population of the whole world.